Increased sizes and improved qualities of tibia bones by myostatin mutation in Japanese quail - Lee, Joonbum; Tompkins, Yuguo; Kim, Dong-Hwan; Kim, Woo Kyun; Lee, Kichoon (Frontiers in Physiology, 2023)
Production of large amounts of meat within a short growth period from modern broilers provides a huge economic benefit to the poultry industry. However, poor bone qualities of broilers caused by rapid growth are considered as one of the problems in the modern broilers industry. After discovery and investigation of myostatin (MSTN) as an anti-myogenic factor to increase muscle mass by targeted knockout in various animal models, additional positive effects of MSTN mutation on bone qualities have been reported in MSTN knockout mice. Although the same beneficial effects on muscle gain by MSTN mutation have been confirmed in MSTN mutant quail and chickens, bone qualities of the MSTN mutant birds have not been investigated, yet. In this study, tibia bones were collected from MSTN mutant and wild-type (WT) quail at 4 months of age and analyzed by Micro-Computed Tomography scanning to compare size and strength of tibia bone and quality parameters in diaphysis and metaphysis regions. Length, width, cortical thickness, and bone breaking strength of tibia bones in the MSTN mutant group were significantly increased compared to those of the WT group, indicating positive effects of MSTN mutation on tibia bone sizes and strength. Furthermore, bone mineral contents and bone volume of whole diaphysis, diaphyseal cortical bone, whole metaphysis, and metaphyseal trabecular and cortical bones were significantly increased in the MSTN mutant group compared to the WT group, indicating increased mineralization in the overall tibia bone by MSTN mutation. Especially, higher bone mineral density (BMD) of whole diaphysis, higher total surface of whole metaphysis, and higher BMD, trabecular thickness, and total volume of metaphyseal trabecular bones in the MSTN mutant group compared to the WT group suggested improvements in bone qualities and structural soundness of both diaphysis and metaphysis regions with significant changes in trabecular bones by MSTN mutation. Taken together, MSTN can be considered as a potential selection marker to not only increase meat yield, but also to improve bone qualities that can reduce the incidence of leg bone problems for the broiler industry.